2022
DOI: 10.1039/d2nr01258h
|View full text |Cite
|
Sign up to set email alerts
|

Efficient iron–cobalt oxide bifunctional electrode catalysts in rechargeable high current density zinc–air batteries

Abstract: Iron-cobalt (FeCo) oxides dispersed on reduced graphene oxide (rGO) were synthesized from nitrate precursors in loading levels from 10 wt% to 60 wt%. These catalysts were tested in lab-scale zinc-air...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Consequently, Co 9 S 8 /Co-N x /CoNi/Ni 3 S 2 @CNS-4 had a tiny E value of 0.72 V, which is compared to the most recently described metal-involving oxygen electrocatalysts (Fig. S10d) 12,18 . In contrast to benchmark Pt/C and RuO 2 , which decreased after the 24 h tests, catalyst 4 performance did not significantly decline after continuous operation for 24 hours at 10 mA cm -2 , according to the long-term durability test, representing that the material had good bifunctional catalytic stability, as shown in Fig.…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 61%
See 1 more Smart Citation
“…Consequently, Co 9 S 8 /Co-N x /CoNi/Ni 3 S 2 @CNS-4 had a tiny E value of 0.72 V, which is compared to the most recently described metal-involving oxygen electrocatalysts (Fig. S10d) 12,18 . In contrast to benchmark Pt/C and RuO 2 , which decreased after the 24 h tests, catalyst 4 performance did not significantly decline after continuous operation for 24 hours at 10 mA cm -2 , according to the long-term durability test, representing that the material had good bifunctional catalytic stability, as shown in Fig.…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 61%
“…S10b). The ORR performance of catalyst Co 9 S 8 /Co-N x /CoNi/Ni 3 S 2 @CNS-4 proved to be better in comparison to recent reported catalysts, in the alkaline electrolyte (Table S1) 12,45,46 . In Fig.…”
Section: Electrochemical Oxygen Reduction Reaction (Orr)mentioning
confidence: 63%
“…[26][27][28][29][30][31][32][33][34] Furthermore, recently, we found that the gap between bifunctional catalytic performance from the electrochemical test (polarization) and battery performance at low current densities does not allow for direct judgment and prediction of the ZAB performance in terms of capacity and cycling stability at higher current densities from the existing literature. 35 Moreover, our nding indicates that the loading of mixed CoFe 2 O 4 and CoO on rGO as catalysts for ZAB evaluated at the current density of 100 mA cm À2 for 60 min charge and 60 min discharge per cycle impacts the battery performance. In the new direction of ZAB operating at such extreme conditions, not only the stability of the battery but also understanding the role of each catalyst components and their contributions to the battery performance are required.…”
Section: Introductionmentioning
confidence: 81%
“…In the new direction of ZAB operating at such extreme conditions, not only the stability of the battery but also understanding the role of each catalyst components and their contributions to the battery performance are required. 35 In this work, we aimed at evaluating the ZAB performance at a high current density of 100 mA cm À2 at each 60 min charge and 60 min discharge per cycle, which are severe conditions, for the rst time. Such a high current density can allow for highrate charge/discharge, which enables high efficient energy storage/conversion for harvesting renewable energies at a large scale or for grid applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation